1975
DOI: 10.1002/j.1537-2197.1975.tb14050.x
|View full text |Cite
|
Sign up to set email alerts
|

Floral Anatomy in the Saxifragaceae Sensu Lato. I. Introduction, Parnassioideae and Brexioideae

Abstract: The floral morphology and anatomy of one representative of the Parnassioideae and two of the Brexioideae are described, and some of the recent literature dealing with the Saxifragaceae sensu lato is reviewed. Comparison of the floral structure in Parnassia to that typical of the Saxifragoideae, the subfamily constituting the Saxifragaceae sensu stricto and which, therefore, may be considered to show the basic saxifragaceous characteristics, reveals little similarity. Parnassia differs in pattern of both sepal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
28
1

Year Published

1975
1975
2005
2005

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 22 publications
1
28
1
Order By: Relevance
“…Smets (1988a) excluded a relationship of the Droserales with Rosales (see Dahlgren, 1983Dahlgren, , 1989Takhtajan, 1980) on the basis of the difference in nectaries. Parnassia (Droseraceae or Parnassiaceae) differs anatomically and ontogenetically (see Klopfer, 1972;Bensel & Palser, 1975a;Saxena, 1976) as well as in stamen morphology (Endress & Stumpf, 1991) from the Saxifragales, where it is often placed. We cannot accept the treatment of Cronquist (1981) either, who groups the insectivorous families Nepenthaceae, Sarraceniaceae and Droseraceae in an order Nepenthales on the basis of similarities in the insectivorous habit.…”
Section: Discussion Of Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation
“…Smets (1988a) excluded a relationship of the Droserales with Rosales (see Dahlgren, 1983Dahlgren, , 1989Takhtajan, 1980) on the basis of the difference in nectaries. Parnassia (Droseraceae or Parnassiaceae) differs anatomically and ontogenetically (see Klopfer, 1972;Bensel & Palser, 1975a;Saxena, 1976) as well as in stamen morphology (Endress & Stumpf, 1991) from the Saxifragales, where it is often placed. We cannot accept the treatment of Cronquist (1981) either, who groups the insectivorous families Nepenthaceae, Sarraceniaceae and Droseraceae in an order Nepenthales on the basis of similarities in the insectivorous habit.…”
Section: Discussion Of Relationshipsmentioning
confidence: 99%
“…Arber (1 9 13) related Parnassia with Hypericum on the basis of similarities in 'stamen fascicles'. Arber (1913) and Bensel & Palser (1975a) interpreted the nectaries of Parnassia as 'staminodial clusters' phylogenetically derived from stamen fascicles, because each 'fascicle' is supplied by single traces, which branch to each division of the nectary. However, we do not believe that the nectaries of Parnassia represent reduced stamen fascicles; the analogy between the stamen fascicles of Hypericum and the branching staminodia of Parnassia is only superficial (see also Weberling, 1989).…”
Section: Discussion Of Relationshipsmentioning
confidence: 99%
“…As a subfamily, it had been a member of Saxifragaceae for a long time (Engler 1930;Thorne 1976;Dahlgren 1980;Cronquist 1981;Ku 1987Ku , 1995Gu and Hultgård 2001). Parnassia was included in Parnassioideae in Droseraceae (Pace 1912;Schoennagel 1931) and was thought to be closely related to Hypericaceae (Arber 1913;Jay 1971) or even 3 Crassulaceae (Bensel and Palser 1975). Recent molecular systematic investigations revealed that Parnassiaceae, including Parnassia and Lepuropetalon Elliott, was a sister group of Celastraceae (Chase et al 1993;Angiosperm Phylogeny Group (APG) 1998;Soltis et al 2000;APG II 2003;Wu et al 2003).…”
mentioning
confidence: 99%
“…Serial microsections of 12 flowers in either cross or longitudinal planes were made and examined. For details of the methods used to prepare the material for examination see Bensel and Palser (1975a) .…”
mentioning
confidence: 99%
“…THIS IS THE FINAL paper of a series reporting on the floral anatomy and morphology of the Saxifragaceae sensu lato. Previous papers have dealt with representatives from seven of the 15 subfamilies in Engler's Saxifragaceae (Bensel and Palser, 1975a, b, c). The present paper includes a description of a representative of the monogeneric Baueroideae of Engler (1928) and a general discussion of how the patterns of variation in floral characteristics throughout the Saxifragaceae sensu lato correlate with the patterns of variation in other types of characters (embryological, biochemical, etc. Long, unicellular, acutely pointed, epidermal hairs are abundant on the pedicel, on the abaxial side of the sepal midrib, and on the surface of the ovary and styles.…”
mentioning
confidence: 99%